Proposal of a Diagnostic Tool for Evaluation of the Organization, Marketing and Financial Areas in Food Processing and Marketing Centers (Ceproma) - Gamboa Naranjo, Melissa (2018)
The Ceproma program was born from the National Food Program. These are business centers administered by small farmers organizations for food industrialization and food marketing, and has the purpose of motivated the small farmers, improve the rural peasant economy and basic food availability, and develop innovated ideas. This diagnosis proposal pretends to support institutional and organization necessities of a Ceproma evaluation tool and make short and long-term decisions. The evaluation tool is based on three areas: organization, marketing and finances. Due to the nature of the Ceproma Program, the evaluation contains a social focus but with economic requirements that each Ceproma has to satisfy to stay in the market. Therefore, the evaluation tool has a mixed nature, considering the social importance and satisfy economic and production requirements.